Daughter of Eve, "Femme Fatale", and Persecuted Artist: The Mythic Transgressive Woman in Oscar Wilde’s and Richard Strauss’s "Salome" - Blackmer, Corinne E (Amaltea. Revista de Mitocrítica, 2016)
Historically, Salome was an unexceptional figure who never catalyzed John the Baptist’s death. However, in Christian Scripture, she becomes the dancing seductress as fallen daughter of Eve. Her stepfather Herod promises Salome his kingdom if she dances for him, but she follows her mother’s wish to have John beheaded. In Strauss’s opera, after Wilde’s Symbolist-Decadent play, Salome becomes independent of Herodias’ will, and the mythic avatar of the femme fatale and persecuted artist who Herod has killed after she kisses John’s severed head. Her signature key of C# major, resolving to the C major sung by Herod and Jokanaan at her death, represent her tragic fate musically.